2015
DOI: 10.1111/jnc.13280
|View full text |Cite
|
Sign up to set email alerts
|

Tph2 gene deletion enhances amphetamine‐induced hypermotility: effect of 5‐HT restoration and role of striatal noradrenaline release

Abstract: Variants of tryptophan hydroxylase-2 (Tph2), the gene encoding enzyme responsible for the synthesis of brain serotonin (5-HT), have been associated with neuropsychiatric disorders, substance abuse and addiction. This study assessed the effect of Tph2 gene deletion on motor behavior and found that motor activity induced by 2.5 and 5 mg/kg amphetamine was enhanced in Tph2 À/À mice. Using the in vivo microdialysis technique we found that the ability of amphetamine to stimulate noradrenaline (NA) release in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Peripheral decarboxylase inhibitors increase central availability of exogenous 5-HTP (Magnussen, 1984) and central levels of serotonin (Itskovitz et al, 1989). However, this finding was unexpected given that the carbidopa is not thought to pass the blood brain-barrier (Porter et al, 1962; Yee et al, 2001), and when administered alone, it has no effect on endogenous central 5-HT, noradrenaline or dopamine in Tph2 knockout mice, nor does it affect 5-HTP or L-DOPA within the cortex or striatum of wild-type mice (Carli et al, 2015). In addition, humans treated with carbidopa, endogenous 5-HTP is not synthesised in sufficient quantity in the periphery to affect brain serotonin functioning (Young et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral decarboxylase inhibitors increase central availability of exogenous 5-HTP (Magnussen, 1984) and central levels of serotonin (Itskovitz et al, 1989). However, this finding was unexpected given that the carbidopa is not thought to pass the blood brain-barrier (Porter et al, 1962; Yee et al, 2001), and when administered alone, it has no effect on endogenous central 5-HT, noradrenaline or dopamine in Tph2 knockout mice, nor does it affect 5-HTP or L-DOPA within the cortex or striatum of wild-type mice (Carli et al, 2015). In addition, humans treated with carbidopa, endogenous 5-HTP is not synthesised in sufficient quantity in the periphery to affect brain serotonin functioning (Young et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that intrinsic 5-HT 2 receptors can modify dopaminergic function (Lucas et al, 2000; Porras et al, 2002) with 5-HT 2 A antagonists reducing hyperactivity induced by amphetamine (O'Neill et al, 1999). In addition, striatal noradrenaline release can modulate the motor effects of amphetamine (Carli et al, 2015). Thus, the observed effects may be related to alterations in the serotonin system, which would require further focused experimental examination.…”
Section: Discussionmentioning
confidence: 99%